The Role of Cardiac Resynchronization Therapy in Heart Failure: A Narrative Review - Olivier Uwishema; Ece Karabulut; Dalal Sheikhah; Burhan Kantawala; Misgana Gallo; Fatima Soufan; Magda Wojtara (Health Science Reports)
ABSTRACT Introduction Structural and functional cardiac defects leading to inadequate tissue oxygenation is known as Heart failure (HF) which is characterized by extensive morbidity and mortality. Pathophysiology of HF involves systolic and diastolic dysfunction, neurohormonal dysregulation, and imbalance in inflammatory mediators which complicates treatment further. Cardiac resynchronization therapy (CRT) is an approach used for restoring ventricular synchrony and enhancing mechanical efficiency. This study discusses various key points of CRT and its uses in HF and discusses challenges and future implications. Methods An extensive review of the literature was conducted with evidence from several databases like Medline, PubMed Central, and Embase. Preference was given to articles published after 2010, but relevant articles even pre‐2010 were included. Mendeley was used as a reference manager for formatting. Results Functional improvements and an enhanced quality of life across a diverse range of patients have been demonstrated using CRT. This has significantly impacted the mortality rates of patients with HF. This manuscript conducted a comparative analysis various hallmark clinical trials conducted in lieu of CRT, across many years (2002, 2003, 2004, 2005, 2017, 2018, 2020). All trials have noted the supremacy of CRT compared to pharmaceutical treatment or other therapeutic methods. Majority of the trial participants had an LVEF of ≤ 35%, a QRS duration of ≤ 150 ms, and were categorized as NYHA class II–IV before initiation of CRT and, posttreatment, LVEF was improved significantly. The main advantages noted were functional improvements, such as enhanced quality of life and reduced mortality. Conclusion There have been multiple efforts undertaken to address the challenges in CRT, which include a reduction in the rates of nonresponding patients and using alternative adjunctive therapies like defibrillators. These have been shown to improve outcomes among HF patients. Although CRT is noted to be very efficient, some challenges like technological limitations, uncertainty regarding optimal pacing, and nonresponding patients, exist. Ongoing research aims to further develop and revolutionize HF care and improve patient outcomes across the world by refining patient selections and CRT efficacy.